Peran brand image sebagai mediasi pengaruh brand ambassador dan social media marketing terhadap minat beli produk - Naumi, Mimi; Hidayat, Candra Wahyu; Sarwoko, Endi (MBR (Management and Business Review), 2023)
This research aims to examine the influence of brand ambassadors and social media marketing on purchasing intention and examine the mediating role of brand image on the influence of brand ambassadors and social media marketing on purchasing intention. Using accidental sampling technique, 112 respondents were selected to fill out the questionnaire, the data was analyzed using path analysis. Research reveals that social media marketing and brand ambassadors have been proven to have a positive influence on purchasing intention both directly and mediated by brand image.